LITERATURE REVIEW : GAMBARAN FAKTOR-FAKTOR PENCETUS ASMA PADA PASIEN ASMA - Jeconiah Gabriello Dandan; Agnes Frethernety; Mual Bobby Enrico Parhusip (Jurnal Kedokteran Universitas Palangka Raya, 2022)
Asthma is a disorder of the respiratory system, which is characterized by intermittent respiratory obstruction, inflammation of the airways and bronchial hypersensitivity. Knowledge of asthma triggers can be useful for people with asthma to avoid factors that can trigger asthma attacks. Knowing the description of the factors that trigger asthma in asthmatic patients. The method used is a systematic review approach, reviewed in a planned and structured manner using an electronic database (Google Scholar, NCBI, PubMed, Europe PMC, Chest Journal and Research Gate) in journal searches, using keywords describing asthma triggers, asthma triggers, asthma , asthma patients, then sorted using inclusion and exclusion criteria and analysis related to data quality (Quality Assessment) using inclusion criteria. There were 17 literatures with findings stating that the trigger factors for asthma in asthmatic patients were exposure to allergens, physical activity, cigarette smoke, weather factors, air pollution, respiratory infections, and psychological factors. The description of asthma trigger factors in asthmatic patients is exposure to allergens, physical activity, cigarette smoke, weather factors, air pollution, respiratory infections, and psychological factors.